Discordance of diabetic retinopathy severity in a cohort of diabetic nephropathy patients: a cross-sectional case-control study in a new Mexican population of type 2 diabetes - Fitzgerald, Ashley; Das, Ryan; Moezzi, Cody J.; Salazar, Savannah R.; Mankad, Rushi; Qualls, Clifford R.; Cabrera, Andrea; Kathuria, Ayushi; Monickaraj, Finny; Tzamaloukas, Antonios; Das, Arup (Frontiers in Endocrinology, 2025)
BackgroundAlthough diabetic retinopathy (DR) and diabetic nephropathy (DN) are well known microvascular complications of diabetes, the correlation between DR and DN remains uncertain. Several studies have suggested differences in etiology and risk factors between these two complications.ObjectivesTo examine whether diabetic retinopathy (DR) and nephropathy (DN) have significant concordance in terms of severity progression in patients with type 2 diabetes.MethodsA case-control study was conducted involving two cohorts of type 2 diabetic patients from a New Mexican population. The cases had confirmed end-stage renal disease (ESRD; Stage 5, on dialysis, eGFR < 15 mL/min, n = 164), while the controls had mild diabetic nephropathy (DN) (Stage 1 or Stage 2, eGFR > 60 mL/min, n = 165). Systemic parameters were collected through retrospective chart reviews, which included HbA1c, blood pressure (BP), lipid levels, serum creatinine (Cr), and retinopathy status determined by dilated fundus examinations. Statistical analyses were conducted, encompassing univariate and multivariate logistic regression analyses for continuous variables, as well as a Chi-squared test for categorical variables.ResultsThe majority (65%) of the ESRD cohort had proliferative diabetic retinopathy (PDR), while 18% of patients exhibited no diabetic retinopathy (DR) or mild non-proliferative diabetic retinopathy (NPDR). Conversely, approximately 38% of the mild DN cohort had PDR. In the univariate analysis, ESRD was significantly associated with lower HbA1c levels (p<0.0001) and higher systolic blood pressure (p<0.0001). Within the ESRD cohort, the onset of PDR was significantly linked to younger age (p=0.0002), higher diastolic blood pressure (p=0.0319), and elevated LDL (p=0.0361). In the multivariate analysis, the development of PDR was inversely related to age (p=0.001, OR=0.95) and positively correlated with serum creatinine (p<0.0001, OR=1.25), systolic blood pressure (p=0.0221, OR=1.023), and albuminuria (p=0.0006, OR=4.65). HbA1c levels showed no significant correlation with the progression of PDR. The use of PDR as a screening tool for chronic kidney disease (CKD) has a sensitivity of 78.68% and a specificity of 51.16%, indicating that it is a suboptimal screening method.ConclusionsOur findings suggest discordance between the progression of diabetic retinopathy and nephropathy.